Simplifying
-1x + -1 = 221 + 2x
Reorder the terms:
-1 + -1x = 221 + 2x
Solving
-1 + -1x = 221 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
-1 + -1x + -2x = 221 + 2x + -2x
Combine like terms: -1x + -2x = -3x
-1 + -3x = 221 + 2x + -2x
Combine like terms: 2x + -2x = 0
-1 + -3x = 221 + 0
-1 + -3x = 221
Add '1' to each side of the equation.
-1 + 1 + -3x = 221 + 1
Combine like terms: -1 + 1 = 0
0 + -3x = 221 + 1
-3x = 221 + 1
Combine like terms: 221 + 1 = 222
-3x = 222
Divide each side by '-3'.
x = -74
Simplifying
x = -74